From syndromic clues to diagnosis: understanding CARD11-driven disorders - García-Martínez, Elena; Schiaffino, María Teresa; Di Natale, Marisa; Díaz Luna, María de las Mercedes; Viteri Álvarez, Daniel Alejandro; Mejía González, María Alejandra (Frontiers in Immunology, 2025)
CARD11 is primarily expressed in hematopoietic tissues and lymphocytes and plays a crucial role in the proper activation of B and T cells in response to antigen recognition. Pathogenic variants in the CARD11 gene result in a broad spectrum of syndromic immunodeficiencies with variable severity and clinical outcomes. Gain-of-function mutations lead to uncontrolled NF-κB activity in lymphocytes and are associated with BENTA syndrome (B-cell Expansion with NF-κB and T-cell Anergy), an autosomal dominant disorder characterized by resistance to conventional therapies used for lymphoproliferative conditions. In contrast, loss-of-function variants are linked to Hyper-IgE-like syndromes, presenting with varying degrees of immunodeficiency—ranging from combined immunodeficiency to specific humoral defects—accompanied by atopic manifestations and autoimmunity. CARD11-associated diseases may be more prevalent than previously recognized due to their clinical overlap with atopic and hematological syndromic disorders. Consequently, a high index of suspicion for these conditions facilitates early diagnosis and enables personalized treatment. In this review, we summarize the broad spectrum of CARD11-related diseases, their underlying pathophysiological mechanisms, multidisciplinary management strategies, and current therapeutic options, along with potential future approaches.